AB1174 ORM2 and APOA2 serum levels can predict oa patient response to chondroitin sulfate/glucosamine hydrochloride: results from the moves study. (15th June 2017) - Calamia, V; Camacho-Encina, M; González-Rodríguez, L; Fernández-Puente, P; Rego-Pérez, I; Herrero, M; Martínez, H; Ruiz-Romero, C; Blanco, FJ
Abstract : Background: A shotgun proteomic analysis performed on sera from patients enrolled in the Multicentre Osteoarthritis interVEntion trial with Sysadoa (MOVES) led to the discovery of a panel of putative predictive protein biomarkers useful to stratify osteoarthritis (OA) patients into responders and non-responders, either to Chondroitin sulfate/Glucosamine hydrochloride (Droglican®, Bioiberica S.A., Barcelona, Spain) or Celecoxib. Objectives: To validate the sensitivity and specificity of a panel of six serum proteins useful to predict the patient response to Droglican treatment, in order to optimize therapeutic outcomes in OA. Methods: We analyzed the serum levels of a panel of six putative predictive protein biomarkers by enzyme-linked immunosorbent assays (ELISAs): APOA2, APOA4, APOH, C4BPa, ITIH1 and ORM2. All the subjects studied belonged to the MOVES cohort at baseline (Droglican sub-cohort, n=260). Non-parametric and multivariate analysis were performed to test the effects of the clinical variables, including gender, age, BMI, radiologic Kellgren/Lawrence (K/L) grade and WOMAC score at baseline, as well as the serum levels of each of the six mentioned proteins, on the response to Droglican treatment according to the OMERACT-OARSI criteria and the WOMAC pain score (20%, 30%, 50% and 70% reduction) recorded at the end of the trial (after 6 months of treatment). Results: Non parametric analysis showed decreased serum levels of ORM2 at baseline in responders to Droglican according to the OMERACT-OARSI criteria compared to non-responders (76, 11±53, 25 vs 104, 25±84, 93; n=171 vs 46; p =0, 047), meanwhile the values for APOA2 appeared statistically increased in responders with a 50% reduction in WOMAC pain score compared to non-responders (79, 95±58, 53 vs 66, 05±46, 49; n=129 vs 112; p =0, 028). Patients with lower levels of ORM2 (median concentration=69, 8 ug/mL) and/or higher level of APOA2 (median concentration=63, 8 ug/mL) showed a markedly better response to pharmacotherapy. Statistical interactions between ORM2 and APOA2 levels and radiologic K/L grade were also detected ( p =0, 048 and p =0, 002 respectively). No statistically significant differences were found for the other four proteins. Conclusions: Our results show that ORM2 and APOA2 levels significantly correlates with patients response to Droglican suggesting the possibility of their use in predictive assays in order to optimize therapeutic outcomes in OA. Validation studies in different cohorts are needed to identify and validate a cut-off point for these biomarkers. Disclosure of Interest: V. Calamia: None declared, M. Camacho-Encina: None declared, L. González-Rodríguez: None declared, P. Fernández-Puente: None declared, I. Rego-Pérez: None declared, M. Herrero Employee of: Bioiberica S.A., H. Martínez Employee of: Bioiberica S.A., C. Ruiz-Romero: None declared, F. J. Blanco: None declared